Influence of Trace H2O and O2 on SF6 Decomposition under Corona Discharge and Spark Discharge based on Oxygen Isotope Tracer - Zhou, Zhenrui; Han, Dong; Zhao, Mingyue; Zhang, Guoqiang (Electrical Insulation Conference and Electrical Manufacturing Expo, 2020)
Lower fluorides of sulfur are primary byproducts of SF 6 when insulation failures occur, which decompose into final long-lived by-products in the presence of oxygen or moisture, such as SO 2 F 2 , SO 2 , SOF 2 and SOF 4 . The decomposition mechanism of SF 6 is complicated, and the decomposition products are different under different insulation failures. Therefore, summarizing a variation of SF 6 decomposition products under different faults and different discharge conditions can provide a reference for fault diagnosis of SF 6 gas-insulated electrical equipment. Based on oxygen isotope tracer technique, different contents of H 2 18 O and 18 O 2 were injected into the text vessel to simulate an environment containing trace moisture or oxygen. Then, a series of corona discharge and spark discharge experiments were carried out. The decomposition gases were detected by gas chromatography-mass spectrometry (GC-MS). The decomposition gases S 16 O 2 F 2 , S 16 O 18 OF 2 , S 18 O 2 F 2 , S 16 O 2 and S 16 O 18 O indicate that moisture and oxygen participate in the decomposition reaction of SF 6 . Furthermore, the influence of trace moisture and oxygen on the contents of three isotopic compounds of SO 2 F 2 were analyzed, and the ratios of SO 2 F 2 to (SO 2 +SOF 2 ) were investigated in the trace moisture environment. The results show that both H 2 O and O 2 involve into the formation of SO 2 F 2 . In the trace moisture environment, the peak area ratio of SO 2 F 2 / (SOF 2 +SO 2 ) gradually decreases with the increase of water injection. The change of the ratio of SO 2 F 2 to (SOF 2 +SO 2 ) may provide an index for detecting the moisture content of SF 6 gas-insulated electrical equipment.